Growth characteristics of 'ikan merah', Lutjanus argentimaculatus (forskal) in Malaysian waters - Ambak, Mohd Azmi; Mohammad Mohsin, A. K.; Mohd Said, Mohd Zaki (Malaysian Society of Applied Biology, 1985)
Growth characteristics of 'ikan merah' (red snapper) were estimated using length frequency data. The von Bertalanffy growth constants tor this species. were k - 0.187. L .= 87.6 cm standard length (S.L.) and to =0.0437 yrs. Six age groups were Identified which are believed to represent 2nd to 7th year classes. The length-weight relationship was also given